Development Scenarios of Sustainability for Golf: The Algarve Case - Antónia Correia; Nuno Videira; Victor Martins; Inês Alves; Catarina Ramires; Rui Subtil (European Regional Science Association (ERSA), 2004)
Golf is becoming a major industry worldwide. The majority of the Portuguese golf courses are located in the Algarve region. Golf tourism has a great economic impact on the Algarve and is regarded by local tourism developers as a vehicle for tackling the seasonal patterns of “mass tourism”. In consideration of the concerns of those involved in regional tourism and golf, the University of Algarve has developed a prospective study on the sustainability paths of this activity, starting from an integrated analysis of the reference conditions of golf in the Algarve, with respect to environmental, economic and social dimensions. This paper presents the sustainability assessment framework developed in this study and the results from its application to the Algarve's golf courses through the definition and evaluation of three alternative development scenarios and their associated impacts. The application of economic, social and environmental indicators was a key tool for the construction of the “baseline”, “moderate” and “intensive scenarios”. It was concluded that the development of further golf activity in the Algarve should be framed within high service and environmental quality standards. The sustainability area for golf course development should vary between 29 and 41 gold courses (equivalent of 18 holes).
Keywords: 330